Asymmetries of the shoulder and pelvic girdles in girls with scoliosis and scoliotic posture - Wilczyński, Jacek (Medical Studies/Studia Medyczne, 2013)
Aim of the research: To evaluate the asymmetries of the shoulder and pelvic girdles in girls aged 7–18 with scoliosis and scoliotic posture. Material and methods: The children were enrolled at the Międzyszkolny Ośrodek Gimnastyki Korekcyjnej i Kompensacyjnej (Interschool Corrective and Compensatory Gymnastics Centre) in Starachowice. The research was carried out in June 2011. 3D digital photogrammetry using the moiré effect was adopted in the research. Depending on the conformity of the variables’ distributions with the normal distribution, and the values of skewness and kurtosis, parametric or non-parametric tests were adopted. The variables were verified in terms of normal distribution with the Shapiro-Wilk test. A screening analysis of the parameters of physiological curvatures of the spine in age groups was also carried out. The relation between the frequency and type of disorders in the frontal plane and age was determined using the χ 2 test. Value of p ≤ 0.05 was assumed as the level of significance. Results: Based on the size of the angle of the curvature of the spine the following were singled out scoliotic posture (1–9°) and idiopathic scoliosis (≥ 10°). There were 21 (75%) children with the scoliotic posture and 7 (25%) with idiopathic scoliosis. The frequency and type of disorders in the frontal plane does not depend on the age of the examined. Asymmetry of the shoulders and shoulder blades was found in all of the examined. The left shoulder along with the left shoulder blade were raised more often. The right side of the pelvis was lowered in most of the examined. Posterior rotation of the left hip bone occurred more often. Conclusions: The values of WBM, WBK and WBC asymmetry coefficients confirm the asymmetry of the shoulder and hip girdles. Analysis of variance did not show any significant relations of asymmetry of the shoulder and hip girdles and the age of the examined.